SOX12 and NRSN2 are candidate genes for 20p13 subtelomeric deletions associated with developmental delay. Issue 8 (6th September 2013) - An, Yu; Amr, Sami S.; Torres, Alcy; Weissman, Laura; Raffalli, Peter; Cox, Gerald; Sheng, Xiaoming; Lip, Va; Bi, Weimin; Patel, Ankita; Stankiewicz, Pawel; Wu, Bai‐Lin; et al.
Abstract 20p13 telomeric/subtelomeric deletions are clinically significant but are currently under‐investigated. So far only five molecularly delineated cases have been reported in literature and no candidate genes have been sufficiently implicated. Here, we present six new deletion cases identified by chromosomal microarray analysis (CMA). We also review 32 cases combined from literature and databases. We found that most 20p13 deletion patients exhibit significant developmental delay. Dysmorphic features are common but a consistent pattern was not recognized. Reduced cognitive ability was frequent. Based on pathogenic deletions delineated in this study, we mapped the smallest overlapping region and identified two nervous system expressing genes (SOX12 and NRSN2) as candidate genes that may be involved in the developmental defects in 20p13 microdeletion. © 2013 Wiley Periodicals, Inc.